Analisis Profil Atap Baja WF dengan Metode LRFD Menggunakan SAP 2000 dan Idea StatiCa - Pribadi, Gali; Rumbyarso, Yonas Prima Arga (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The roof is one of the main components in a building to protect it from heat and rain. The roof is also an architectural component that adds to the beauty of a building. Therefore, every building must have a roof. Currently, many steel roofs are used as the structural frame. Considering that wooden materials are considered expensive to use nowadays. Apart from that, steel material has a longer durability than wood material, so steel is considered the best alternative at the moment. The title of this article is "Structure Analysis of WF Steel Profile Roofs Using the LRFD Method". This analysis was carried out to determine the strength of the WF steel truss structure and its connections. The analysis method used in this research is the LRFD method which is carried out with the help of the SAP 2000 v20 program to calculate the statics of the roof construction and using the help of the Idea StatiCa program to calculate the connections. Based on the results obtained, the trusses that use the WF 200.100.5,5.8 profile are able to withstand the forces acting on the truss structure, and the connections are sufficient to withstand the forces that occur.